Oesophageal eosinophilia and oesophageal diseases in children: are the limits clear? - Angel A Escobedo; Oscar Manuel Villa Jiménez; Sarah Esther Diaz-Oliva; Idalmis Aguilera-Matos (BMJ Publishing Group, 2020)
Gastro-oesophageal reflux disease, eosinophilic oesophagitis and oesophageal motility disorders are among the most common diseases accompanying oesophageal eosinophilia. They have similarities and their limits are frequently not well defined. This article reviews the main characteristics relating to their similarities and differences, highlighting existing controversies among these diseases, in addition to current knowledge. In the case of a patient with symptoms of oesophageal dysfunction, it is suggested to carry out an integral analysis of the clinical features and diagnostic test results, including histology, while individualising each case before confirming a definitive diagnosis. Future investigation in paediatric patients is necessary to assess eosinophilic infiltration in the various layers of the oesophageal tissue, along with its clinical and pathophysiological implications.